The influence of N6-methyladenosine (m6A) RNA methylation on synaptic function and local protein synthesis - Martinez De La Cruz, Braulio (2020)
Leading theories on learning and memory postulate the importance of strengthening specific synaptic pathways, communication of post- and pre-synaptic terminals, and dendritic local protein synthesis. RNA-binding proteins which recognise epigenomic N6-methyladenosine (m6A) messenger RNA modifications can regulate a number of molecular functions including polyribosome loading, RNA decay, splicing, and translation. To investigate whether and how synaptic plasticity may be regulated by m6A RNA processing, three approaches were undertaken.